2019
DOI: 10.24200/sci.2019.51354.2132
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of The New Excitation Controlled Synchronous Generator-Based Wind Turbine

Abstract: Excitation Controlled Synchronous Generator-based Wind Turbine (ECSG WT) is a recently proposed wind turbine scheme which has not been fully investigated in detail. This paper is devoted to analyze performance of the ECSG WT scheme and to compare it with two mainstream wind turbine schemes based on electrically excited synchronous generator, i.e. VSC-based full converter wind turbine and diode bridge rectifier-based wind turbine equipped with boost converter on its DC link. The aim of this comparison is to dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…In [20], the authors suggested the enhancement of the surface of flange shrouded wind turbine to optimize the energy harvest. Shamsnia and Parniani compared the performance of the new excitation controlled synchronous generator-based wind turbine with electrically excited wind turbine to show that the proposed new structure is promising in terms of economic, reliability, and efficiency [21]. Abedini et al investigated the microgrids including power plant and two wind turbines with all possible realworld assumptions as purpose of educational courses [22].…”
Section: Introductionmentioning
confidence: 99%
“…In [20], the authors suggested the enhancement of the surface of flange shrouded wind turbine to optimize the energy harvest. Shamsnia and Parniani compared the performance of the new excitation controlled synchronous generator-based wind turbine with electrically excited wind turbine to show that the proposed new structure is promising in terms of economic, reliability, and efficiency [21]. Abedini et al investigated the microgrids including power plant and two wind turbines with all possible realworld assumptions as purpose of educational courses [22].…”
Section: Introductionmentioning
confidence: 99%